Evaluating the potential impact of a reformulated version of oxycodone upon tampering, non‐adherence and diversion of opioids: the National Opioid Medications Abuse Deterrence (NOMAD) study protocol. (30th October 2014) - Degenhardt, Louisa; Larance, Briony; Bruno, Raimondo; Lintzeris, Nicholas; Ali, Robert; Farrell, Michael
Abstract Aims A new oxycodone formulation (Reformulated OxyContin®) was released in Australia, early 2014. It was developed as a tamper‐resistant ('abuse‐deterrent') formulation of the drug. We summarize methods used in the National Opioid Medication Abuse Deterrence (NOMAD) study, which will examine: (i) whether there is a reduction in extra‐medical use (including via tampering) of OxyContin® following the introduction of Reformulated OxyContin®; (ii) potential changes in extra‐medical use of non‐abuse‐deterrent forms of oxycodone, other pharmaceutical opioids and illicit drugs; (iii) whether methods of tampering with Reformulated OxyContin® become widespread over time; (iv) Reformulated OxyContin®'s attractiveness on the illicit market; and (v) sales, prescriptions and harms related to OxyContin® and other drugs. Methods There are three major components. First, analyses of existing routine data sources such as: pharmaceutical sales; prescribing data; data on drug overdose deaths; and survey data on drug use in the general population and among people who inject drugs; secondly, specific data on OxyContin® collected through the Illicit Drug Reporting System; and thirdly, a prospective cohort of n = 606 people who regularly misuse or tamper with pharmaceutical opioids was formed prior to the introduction of Reformulated OxyContin®, followed‐up twice post‐release to examine potential changes after Reformulated OxyContin®'s introduction. Discussion The study's strengths lie in varied data collections; interrupted time–series analysis; and prospective cohort. To our knowledge, this is one of the most comprehensive and transparently conducted studies conducted to date of the potential impact of an opioid medication upon use, tampering and diversion. Results have the potential to inform policymakers, clinicians, consumers and researchers alike.